Hierarchical evaluation framework for coupling effect enhancement of renewable energy and thermal power coupling generation system. (March 2023) - Zou, Yao; Wang, Qianggang; Hu, Bo; Chi, Yuan; Zhou, Guiping; Xu, Fei; Zhou, Niancheng; Xia, Qinqin
Highlights: RETCS is a VPP that aggregates renewable energy and thermal power to the main power system through the coupling point, power sources in RETCS can coordinate as an integrated generation to improve efficiency. The proposed coupling coordination degree (CCD) evaluation framework can effectively assess the RETCS from resource, economy, and environment subsystems. The proposed stochastic RETCS planning model and CCD evaluation framework can investigate appropriate coordination strategies and power demand to improve the coupling effect of RETCS. Abstract: Renewable energy and thermal power coupling generation system (RETCS) is a special virtual power plant that aggregates renewable energy and thermal power to the main power system through the coupling point. RECTS can coordinate as an integrated system to handle the power fluctuation of renewable energy. Analyzing the interaction of RETCS in resource, economy, and environment comprehensively is the key to improving the coupling effect of the system. This work proposes a coupling coordination degree (CCD) evaluation system to assess and improve the coupling effect of the RETCS. First, CCD evaluation system is established to assess the RETCS using indicators from resource, economy, and environment subsystems in detail. Second, a stochastic RETCS planning model is established to investigate the coordination strategy of the system. Finally, a RETCS case study with different wind power penetration levels and power demand in northeast China is carried out to demonstrate the effectiveness of CCD evaluation system in representing the coupling effect of RETCS and helping to improve the system. Numerical results show that thermal units with deep peak regulation capability can better utilize the ramping and power regulation potential to handle the wind power fluctuation in most cases. An appropriate power source capacities in RETCS can improve the coupling effect of the system under a certain power demand.